Partners in command George Marshall and Dwight Eisenhower in war and peace - Perry, Mark 1950-
Partners in command is an extraordinary portrait of an often ignored - and misunderstood - alliance between two iconic figures and the ways in which their unusual partnership would ultimately shape fifty years of successful American foreign policy